The selective autophagy receptor SQSTM1/p62 improves lifespan and proteostasis in an evolutionarily conserved manner. Issue 4 (2nd April 2020) - Aparicio, Ricardo; Hansen, Malene; Walker, David W.; Kumsta, Caroline
ABSTRACT: The degradation of specific cargos such as ubiquitinated protein aggregates and dysfunctional mitochondria via macroautophagy/autophagy is facilitated by SQSTM1/p62, the first described selective autophagy receptor in metazoans. While the general process of autophagy plays crucial roles during aging, it remains unclear whether and how selective autophagy mediates effects on longevity and health. Two recent studies in the nematode Caenorhabditis elegans and the fruit fly Drosophila melanogaster observed gene expression changes of the respective SQSTM1 orthologs in response to environmental stressors or age and showed that overexpression of SQSTM1 is sufficient to extend lifespan and improve proteostasis and mitochondrial function in an autophagy-dependent manner in these model organisms. These findings show that increased expression of the selective autophagy receptor SQSTM1 is sufficient to induce aggrephagy in C. elegans, and mitophagy in Drosophila, and demonstrate an evolutionarily conserved role for SQSTM1 in lifespan determination.